Persistence in the Passion Investment Market - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Alex Plastun; Ahniia Havrylina (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper uses R/S analysis and fractional integration techniques to investigate persistence in the passion investment market. Specifically, it analyses 3 fine wine price indices, 10 diamond price indices, 15 art price indices, and 1 stamp price index at the daily, monthly and quarterly frequency. The results can be summarised as follows: wine prices are found to be highly persistent, whilst stamp prices appear to be only weakly persistent, though they can still be characterised as a long-memory process; as for diamond prices, they can be persistent (Diamonds & Gems), anti-persistent (Diamonds Carat indices) or even random (Polished Prices Diamond Index). The dynamic R/S analysis also shows that persistence is time-varying and tends to fluctuate around the average. These findings can be explained by the different degree of liquidity of the assets examined.
Keywords: C22; G12; 330; passion investment; persistence; long memory; R/S analysis; fractional integration